Pembinaan Pemandu Wisata Berbahasa Inggris dan Pelatihan Drama Tari Dewa Mesraman dalam Upaya Mengembangkan Wisata Budaya Desa Paksebali - Ni Ketut Dewi Yulianti; Ni Wayan Mudiasih; Ni Wayan Suratni; Komang Wahyu Dinata (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2023)
Community Service (PKM) is one of the three dharmas in the Tridharma of Higher Education which is tasked with making the life of the nation and state intelligent and advancing the welfare of society by utilizing educational knowledge in addition to the dharma of research and the dharma of education and teaching. Based on this, ISI Denpasar in 2023 will carry out PKM activities in Paksebali village, Klungkung Regency with the activity title "Developing English Speaking Tour Guides and the Dewa Mesraman Dance Drama in Efforts to Develop Paksebali Village Culture in Klungkung Regency". The method of implementing activities in PKM is carried out in three stages, namely: planning, implementation and evaluation. The purpose of this article is to discuss the process of Paksebali village PKM activities and the outcomes achieved in these activities. This PKM activity produced an English speaking tour guide and the Dewa Mesraman dance drama which was made into a video recording and published on YouTube.